2005
DOI: 10.1111/j.1365-2044.2004.04067.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid and serum concentrations of beta‐trace protein during pregnancy

Abstract: SummaryWe conducted a prospective observational study among a cohort of 40 term parturients undergoing spinal anaesthesia for elective Caesarean section, to determine the concentration of b-trace protein in cerebrospinal fluid (CSF) and serum. Serum and CSF samples, taken at the time of dural puncture, were assayed by nephelometry. The mean serum b-trace protein concentration was 0.39 mg.l )1 and the mean CSF concentration was 27.9 mg.l )1 , giving a mean ratio of CSF to serum concentration of 76. This ratio i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
1
10
1
Order By: Relevance
“…The discrepancy between our finding of low CSF L-PGDS levels (which has been replicated in repeated measurements) and the recent report of increased serum levels in narcoleptic patients cannot be explained yet [11]. The finding of discrepant serum and CSF L-PGDS concentrations was recently found to be useful to detect CSF leaks [12]. Similarly, earlier reports found that CSF L-PGDS levels can be used in conjunction with CSF/serum albumin ratio to distinguish between different neurological pathologies associated with CSF protein increase and blood-brain barrier dysfunctions [13].…”
Section: Discussioncontrasting
confidence: 80%
“…The discrepancy between our finding of low CSF L-PGDS levels (which has been replicated in repeated measurements) and the recent report of increased serum levels in narcoleptic patients cannot be explained yet [11]. The finding of discrepant serum and CSF L-PGDS concentrations was recently found to be useful to detect CSF leaks [12]. Similarly, earlier reports found that CSF L-PGDS levels can be used in conjunction with CSF/serum albumin ratio to distinguish between different neurological pathologies associated with CSF protein increase and blood-brain barrier dysfunctions [13].…”
Section: Discussioncontrasting
confidence: 80%
“…16,18 -20) L-PGDS/ β-trace is also abundant in various types of biological fluids such as cerebrospinal fluid, ascites, seminal plasma, and amniotic fluid. [21][22][23][24][25][26] Although the biological role of this enzyme or its prostanoid product remains unclear, several studies have shown L-PGDS to be increased in patients with renal insufficiency, 13,27,28) diabetes mellitus, 29,30) hypertension, 31) angina 32) and osteoarthritis. 33) In addition, Taba et al 34) showed that laminar shear stress loading onto endothelial cells caused increased expression of mRNA for L-PGDS.…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandin D synthase (PGD synthase) is an abundant brain‐specific protein and is used as a marker of CSF during fetal development (McArthur et al. 2005).…”
Section: Discussionmentioning
confidence: 99%